2018
DOI: 10.1002/anie.201808676
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogenation of Cyclic Carbonates using Manganese Complexes

Abstract: Catalytic hydrogenation of cyclic carbonates to diols and methanol was achieved using a molecular catalyst based on earth‐abundant manganese. The complex [Mn(CO)2(Br)[HN(C2H4PiPr2)2] 1 comprising commercially available MACHO ligand is an effective pre‐catalyst operating under relatively mild conditions (T=120 °C, p(H2)=30–60 bar). Upon activation with NaOtBu, the formation of coordinatively unsaturated complex [Mn(CO)2[N(C2H4PiPr2)2)] 5 was spectroscopically verified, which confirmed a kinetically competent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 43 publications
1
61
0
Order By: Relevance
“…Driven by the importance of enantiopure alcohols, [2] iron catalysts have been developed for the asymmetric hydrogenation of polar double bonds. [3][4][5][6][7] In contrast, manganese remained unexplored until 2016, when it was applied in the non-enantioselective hydrogenation of polar multiple bonds with H 2 [8][9][10][11][12][13][14][15] and, more rarely,u nder hydrogen-transfer conditions. [16][17][18] Similarly,e nantioselective Mn I catalysts for ketone hydrogenation with H 2 (Clarke: A, [19] Beller: B, [20] Han and Ding: C, [21] and ours: D [22] )a re more numerous than those for asymmetric transfer hydrogenation (E [23] and F [24] ; Figure 1).…”
mentioning
confidence: 99%
“…Driven by the importance of enantiopure alcohols, [2] iron catalysts have been developed for the asymmetric hydrogenation of polar double bonds. [3][4][5][6][7] In contrast, manganese remained unexplored until 2016, when it was applied in the non-enantioselective hydrogenation of polar multiple bonds with H 2 [8][9][10][11][12][13][14][15] and, more rarely,u nder hydrogen-transfer conditions. [16][17][18] Similarly,e nantioselective Mn I catalysts for ketone hydrogenation with H 2 (Clarke: A, [19] Beller: B, [20] Han and Ding: C, [21] and ours: D [22] )a re more numerous than those for asymmetric transfer hydrogenation (E [23] and F [24] ; Figure 1).…”
mentioning
confidence: 99%
“…For a broad range of primary and secondary alcohols as substrates, the methyl group is introduced selectively in β ‐position providing the branched products in good to very high yields with water as the only byproduct (Scheme ). The synthetic methodology has been transferred and largely extended by the use of Mn(I)‐MACHO complex most recently . In this work we present a mechanistic analysis of this transformation with the original ruthenium catalyst based on experimentally and theoretically compiled data.…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneous catalysts able to convert cyclic organic carbonates with high selectivity have also been reported by other groups (Supporting Information, Table S1) . Very recently, three examples of homogeneous catalysts based on a non‐noble metal center (manganese) have been reported that transform organic carbonates into diols and methanol in high yields (Supporting Information, Table S1) …”
Section: Figurementioning
confidence: 99%